Trends in pulmonary embolism mortality in cancer patients in the United States from 1999-2022– A CDC Wonder database study - Elizabeth Dort; Hannah Rud; Taylor Billion; Abubakar Tauseef (Respiratory Research)
Abstract Background Pulmonary embolism (PE) is the third leading cause of cardiovascular death in the United States (Thromb Res. 2023;223:53–60) and presides as a major cause of morbidity and mortality among cancer patients. We investigated the trends of PE-related mortality in cancer patients over the last two decades. Methods This retrospective analysis of the Centers for Disease Control’s Wide-ranging Online Data for Epidemiologic Research (CDC WONDER) database focused on PE-related mortality in cancer patients across the United States from 1999 to 2022. Mortality in adults with PE and cancer was analyzed. Age-adjusted mortality rates (AAMRs) per 100,000 persons and annual percent change (APC) and average annual percent changes (AAPCs) were calculated and reported. Results There were 214,756 total deaths due to PEs in cancer patients in the United States between 1999-2022. The overall mortality trend increased over time, with an annual percent change increase from 0.61 (95% CI 0.29 to 0.88)* from 1999-2016 to 5.77 (95% CI 4.68 to 7.41)* in 2016–2022 and an average annual percent change (AAPC) of 1.93 (95% CI 1.72 to 2.13). A notable mortality increase was seen across gender, race/ethnicity, age, and regional factors beginning in 2016 and continuing through 2022. Additionally, PE-related mortality was significantly higher in the male, Black, and 85 + years old populations. The Midwest and rural regions had the highest PE-related mortality rates as well. Conclusion There is an overall increasing trend in PE-related mortality for cancer patients, with a remarkable increase in 2016. This study highlights the specific populations and regions most affected by PE-related mortality emphasizing the need to increase education, timely management, and address disparities for these patients.